LATE CARBONIFEROUS BRACHIOPODS FROM KARAKORUM, PAKISTAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Carboniferous rocks from North Karakorum display sharp lateral variations in lithology and thickness suggesting accumulation in half-grabens during continental rifting between the Karakorum block and northern Gondwana. Different Carboniferous successions, belonging to distinct tectonic units, have been detected. Thin, poorly fossiliferous successions of arenites and crinoidal limestones contrast with very thick terrigenous-carbonate successions comprising two distinct fossiliferous horizons. The lower fossiliferous horizon yielded brachiopods (Pustula sp., Rhipidomella sp., Choristites sp., Martiniopsis sp., Afghanospirifer sp., Gypospirifer sp., Composita sp.) of Bashkirian age. The upper fossiliferous horizon, lying about 90 m above the former, contains corals, crinoids and brachiopods (Densepustula cf. losarensis, Dowhatania sulcata n. sp., Brachythyris sp., Rhipidomella sp., Septacamera dowhatensis, Alispirifer middlemissi) of Moscovian to Kasimovian age. The Carboniferous brachiopods of North Karakorum are similar to those collected in the Late Carboniferous of Central Afghanistan, Himalaya (Manang, Spiti, Tibet), and Lhasa Block (Xainza area).